A queen odour mediates reproductive suppression in a eusocial mammal - Mohammed A. Khallaf; Daniel W. Hart; Wenhan Luo; Firdevs Murad; Felipe Cybis Pereira; Daniel Mendez-Aranda; Nicole Hagenah; Alice Rossi; Valérie Bégay; Jan Okrouhlík; Dietmar Krautwurst; Mungo Kisinza Ngalameno; et al. (Nature, 2026)
Abstract Eusociality is exceptionally rare in mammals, and its proximate mechanisms remain poorly understood. Naked mole-rats provide a striking example, with reproduction restricted to a single queen, while all other females remain infertile 1 . Here we identify a chemical signal in queens that can regulate this reproductive hierarchy. Isopropyl myristate is a low-volatility ester that is enriched in queens and nearly absent from non-breeding animals. Isopropyl myristate is detected by peripheral and central olfactory neurons and elicits avoidance in high-ranking animals. Exposure alters levels of prolactin and progesterone in non-breeders to suppress reproduction. Daily addition of isopropyl myristate to a queenless colony prevented queen succession, whereas withdrawal triggered aggression and reproductive competition. Isopropyl myristate was also detected in breeding females of several Fukomys mole-rat species, but reaches higher levels in naked mole-rats, paralleling their extreme reproductive skew. These findings reveal a chemical cue that can mediate reproductive suppression in a mammal, linking insect and mammalian eusociality.